PENAKSIR RANTAI RASIO-CUM-DUAL UNTUK RATA-RATA POPULASI PADA SAMPLING GANDA - Hollan Manalu; Bustami '; Haposan Sirait (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2015)
This article discusses three chain estimators for population mean using double sampling, which is a review article from Choudhury and Singh [Statistics In Transition-new series 2012: 519-536]. The three estimators are biased estimators, then their mean square errors are determined. Furthermore, the mean square errors are compared to the mean square error of each estimator. This comparison shows that the estimator having thesmallest mean square error is the most efficient estimator.